Reduction of tethering distance by papillary muscle tugging approximation with mitral valve replacement for non-ischemic functional mitral regurgitation induces left ventricular reverse remodeling - Ishigaki, Takahiro; Wakasa, Satoru; Shingu, Yasushige; Ohkawa, Yohei; Yamada, Akira; Anzai, Toshihisa; Matsui, Yoshiro (Journal of cardiology, 2022)
•Left ventricular (LV) remodeling causes mitral valve tethering and regurgitation.•If advanced, LV remodeling can be irreversible by mitral valve procedure alone.•Surgical anti-tethering by subvalvular procedure could induce LV reverse remodeling. Functional mitral regurgitation (FMR) is caused by left ventricular (LV) remodeling and subsequent tethering of the mitral valve (MV). If LV remodeling is irreversibly advanced, it could not be attenuated by the MV procedure alone, although the additional subvalvular procedure could induce LV reverse remodeling by forcibly reducing MV tethering. This study aimed to assess the anti-tethering effect of papillary muscle tugging approximation (PMTA) on LV reverse remodeling after mitral valve replacement (MVR) for non-ischemic FMR. The study subjects were 19 patients who underwent MVR with and without PMTA [MVR + PMTA (n = 11) and MVR alone (n = 8), respectively] for non-ischemic FMR. The tethering distance (TD) and LV end-systolic volume (ESV) at the preoperative, postoperative, and follow-up periods were assessed in terms of their correlation and time-dependent changes. The intra-LV energy efficiency was also evaluated through vector flow mapping analysis. TD and ESV were comparable between both procedures preoperatively and did not change after MVR alone. In MVR + PMTA, however, a significant decrease was identified in TD and ESV at the early postoperative and follow-up periods, respectively [TD = 48, 30, and 31 mm (p < 0.001) and ESV = 159, 133, and 82 mL (p < 0.001) at the preoperative, postoperative, and follow-up periods, respectively]. Finally, at follow-up, the extent of change from the preoperative value in ESV significantly correlated with that in TD (ρ = 0.81, p < 0.001 for overall; ρ = 0.93, p < 0.001 for MVR + PMTA; ρ = 0.86, p = 0.011 for MVR alone). The ratio of TD to ESV was also significantly correlated with systolic energy loss to LV stroke work after MVR + PMTA (ρ = 0.81, p = 0.015). PMTA for non-ischemic FMR could induce LV reverse remodeling depending on the extent of postoperative TD reduction. A smaller TD to ESV was associated with a higher intra-LV energy efficiency after PMTA + MVR. Surgical anti-tethering by PMTA could induce LV reverse remodeling after MVR for non-ischemic FMR, depending on the extent of reduction of the tethering distance. FMR, functional mitral regurgitation; LV, left ventricle; MVR, mitral valve replacement; PMTA, papillary muscle tugging approximation. [Display omitted] .